Effect of Aloe Vera Drink with Cinnamon on Blood Sugar Reduction in Families with Type II Diabetes Mellitus in East Jakarta - Yuli Astuti; Muhammad Fandizal; Nova Riani; Aditya Rizki Ramadhan; Windy Ayu Ariastika (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2021)
Introduction: Diabetes Mellitus is a disease caused by an increase in blood sugar (glucose) levels. Increased glucose in the blood can occur because the hormone insulin does not succeed in bringing our glucose into the body's cells. The incidence of diabetes in the world shows an increasing prevalence every year. Uncontrolled diabetes can cause disorders of the nerves, kidneys, eyes, and heart blood vessels. To control blood sugar, you can use natural remedies, namely aloe vera and cinnamon which have hypoglycemic properties. Objective: This study was to determine whether aloe vera drink with cinnamon has an effect on lowering blood sugar. Methods: This research method uses a quasi-experimental design with a nonequivalent control group design. The experimental group was given treatment while the control group was given a placebo treatment. In the treatment and control groups, it begins with a pre-test/blood sugar measurement, after giving the treatment a post-test/blood sugar measurement is conducted. Results: The average blood sugar of respondents after consuming cinnamon water was 136 mg/dl while the average blood sugar of respondents after consuming aloe vera cinnamon water was 111 mg/dl. This shows that more respondents had a significant drop in blood sugar after consuming aloe vera cinnamon water. Conclusion: Consumption of aloe vera and cinnamon drinks can reduce blood sugar in patients with type II diabetes mellitus.